Above chaos, quest, and restitution: narrative experiences of African immigrant youth's settlement in Canada - Roberta Lynn Woodgate; David Shiyokha Busolo (BMC, 2018)
Abstract Background African Immigrant and refugee youth represent an increasing group of newcomers in Canada. Upon their immigration, youth experience challenges that have the potential to lead to poor health, yet little is known about their settlement journey. Accordingly, this qualitative study examines the settlement journey of African immigrant and refugee youth with a focus on how their experiences were shaped by the social determinants of health. Methods We conducted a total of 70 interviews with 52 immigrant and refugee youth (ages 13-29 years) who had arrived in Canada in the preceding six years. Qualitative data was analyzed using Frank's dialogical narrative analysis approach (Frank AW, Practicing Dialogical Narrative Analysis. In: Varieties of Narrative Analysis, 2016). Results Youth experienced different settlement journeys that are described in the three narrative typologies of chaos, quest, and restitution. The chaos narrative of a long road ahead revealed the themes of 'facing challenges' and 'still the outsider.' The quest narrative of not there yet was represented by the themes of 'stepping out of your comfort zone' and 'being relentless.' The theme of 'supportive environments' depicted the restitution narrative of dreams become a reality. Youth highlighted the impact of social determinants of health in their settlement. Conclusion Youth experienced different settlement journeys that were mired in chaos and challenges. However, youth were more likely to experience restitution when they received social support and found a sense of belonging. In future, policies and programs that seek to improve immigrant and refugee youth's settlement experiences need to be multifaceted, offer more support and promote a sense of belonging.